2002
DOI: 10.1002/mma.330
|View full text |Cite
|
Sign up to set email alerts
|

On singular mono‐energetic transport equations in slab geometry

Abstract: SUMMARYIn this paper we establish the well posedness of the Cauchy problem associated to transport equations with singular cross-sections (i.e. unbounded collisions frequencies and unbounded collision operators) in L 1 spaces for specular re ecting boundary conditions. In addition, we discuss the weak compactness of the second-order remainder term of the Dyson-Phillips expansion. This allows us to estimate the essential type of the transport semigroup from which the asymptotic behaviour of the solution is deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…We only mention the recent results of [13] dealing with the asymptotic behavior of the solution to (5.1)-(5.2) as well as [6,7] which take into account possibly unbounded collision operator K. In the L p -setting, our main result generalizes the existing ones:…”
Section: Transport Equations In Slab Geometrymentioning
confidence: 58%
“…We only mention the recent results of [13] dealing with the asymptotic behavior of the solution to (5.1)-(5.2) as well as [6,7] which take into account possibly unbounded collision operator K. In the L p -setting, our main result generalizes the existing ones:…”
Section: Transport Equations In Slab Geometrymentioning
confidence: 58%
“…is continuous and tends to zero as λ → +∞ so that, by (10), there exists λ > s(− + C m 1 ) such that…”
Section: Corollarymentioning
confidence: 96%
“…In [2] and [3], M. Chabi and K. Latrach showed that the streaming operator T H , defined in (6), generates a positive C 0 -semigroup (U H (t)) t 0 on X p given explicitly by (7); and, under conditions (A1) and (A2) the singular transport operator A H := T H + K generates a positive C 0 -semigroup (V H (t)) t 0 given by the Dyson-Phillips expansion defined on D(T H ):…”
Section: Introductionmentioning
confidence: 96%
“…Let us assume the two following assumptions on the collision frequency σ (·) and the collision operator K : This work was motivated by the earlier works of M. Chabi and K. Latrach [2,3] and M. Chabi and M. Mokhtar-Kharroubi [4] where neutron transport equations with unbounded collision operators were investigated on L p spaces, with 1 p < +∞. Their goal was to discuss the well-posedness and time structure (t → ∞) of the solution to the time-dependent problem (1) supplemented by the specular reflection boundary conditions:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation